Usability Evaluation for the Integration of Library Data Analysis and an Interactive Artwork by Sensing Technology - Yuh-Shihng Chang; Kuo-Jui Hu (Applied Sciences, 2020)
In this research, we propose innovative ideas for digital art combined with educational applications for the library. It also presents the library’s information services to be more humane and interesting. By taking interactive devices as the basis, this research integrates college library borrowing data and an interactive artwork in order to perform an information visualization service for a user in the library by using their own smart phone. This research uses an instant data operation to carry out the information inquiry applications to present three years of library borrowing data, from 2013 to 2015, obtained from the Hsih Shin University library Data Access Protocol. Finally, a usability evaluation for the interactive art is conducted. To testify that this interactive art design meets the principle of user acceptance, a questionnaire survey is used for the statistical verification. The research findings show that a positive explanation value was achieved for user acceptance. The research model proposed by this research acts as a usability evaluation of the integrated application of an interactive artwork and library information service. The research model also corresponded to the user’s emotional feedback in the HCI research field. The value of this research is that we provide usability-verified models for cross-domain applications.